CLINICAL AND FUNCTIONAL FEATURES IN COURSE CHRONIC PANCREATITIS WITH ACCOMPANYING DUODENOSTASIS - Ya. M. Vahrushev; A. A. Lebedev (Архивъ внутренней медицины)
The aim. Research the clinical features, functional state of duodenum among patients with chronic pancreatitis and accompanying duodenostasis.Materials and methods. The clinical course of chronic pancreatitis with accompanying duodenostasis (85 cases) and isolated chronic pancreatitis (56 cases) has been studied. Along with the general clinical data the study includes the results of exocrine pancreatic function examination (fecal elastase-1, blood alpha amylase and lipase) and its endocrine function (insulin and С-peptide). Regulating hormonal factors (gastrin and somatotropin) have been studied. Was used results of rentgenology and endoscopic examinations, intraduodenal manometry results in verification of duodenostasis.Results. In the observation group resistant pain syndrome was revealed in 93% cases (at patient with isolated pancreatitis in 57% cases) and in more degree was expressed coprological syndromes (amilorhea in 82,29% cases, creatorhea in 82,14% cases, steatorhea in 87,5% cases). In the observation group were significantly more diagnosed hyperperistaltic (in 88% cases of observation group and in 9,4% cases of the comparison group) and duodenal hypertension (in 22% cases of observation group and in 0.0% cases of the comparison group). The phenomenon of «semolina» was reveals more often in observation group (in 31,9% cases of observation group and in 5% cases of the comparison group).Among patients with chronic pancreatitis and accompanying duodenostasis decrease the level of C-peptid and increase secretion of insulin, somatotropin and gastrin.Conclusion. It reveals that according to the comprehensive clinical and functional investigation chronic pancreatitis with accompanying duodenostasis gets a more severe course in comparison with isolated pancreatitis.